(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
In forensic situations, bodies are brought from different water bodies then many questions about source of water at original spot are very important. The main issues of Ante-mortem drowning and postmortem submersions queries have to be resolved. Weed are present in most of the water bodies whether it is sea, river, lake, ponds or any other type of water collection on land. If we examine these weeds and small aquatic animals closely then some hint about source of water and other related questions can be answered by autopsy surgeons in objective manner. In this regard basic information about these weeds is given in the article.